Implementing competency‐based education in multiple programs: A workshop to structure and monitor programs' priorities using ADDIE. Issue 3 (18th July 2021) - Lafleur, Alexandre; Babin, Marie‐Julie; Michaud‐Couture, Claudie; Lacasse, Miriam; Giguère, Yves; Cantat, Adrien; Allen, Christyne; Gingras, Nathalie
Abstract: Context: All Canadian postgraduate medical programs are implementing the major components of competency‐based education. To do so, our institution had to provide individualized training and monitoring for all our programs. Innovation: We organized half‐day workshops with four work sessions: core competencies, competency portfolio, curriculum mapping, and competence committee. Program teams decided their priority tasks after each work session. We classified tasks into ADDIE pedagogical design stages (Analysis, Design, Development, Implementation, Evaluation). We conducted interviews at 12 months. Results: Programs ( n = 29) prioritized mainly tasks of Design (37% of tasks), Development (24%) and Analysis (21%). At 12‐month follow‐up ( n = 17), 20% of the tasks were initiated, 22% reached a higher stage, 33% reaching Implementation/Evaluation. Programs needed material and financial resources for Analysis/Development tasks, and faculty training for Implementation/Evaluation tasks. Conclusion: Work sessions provided a structure to commit to priority tasks. Their classification into ADDIE stages systematized the monitoring and the search for solutions.